ANALYSIS OF FACTORS INFLUENCING QUALITY CULTURE AND THEIR IMPACT ON ORGANIZATIONAL DEVELOPMENT - Kairiša, Ilze; Lapiņa, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Total quality management is an approach geared towards the organization’s efforts to continuously improve its ability to provide its customers with high quality products and services. In order for the organization to be able to ensure efficient use of resources, increase productivity and maintain excellent quality, it is necessary to develop quality culture. The aim of the research is to study and analyse the quality culture factors that might influence the continuous improvement and development of the organization’s activities. The research is based on the study of quality culture factors using literature review, qualitative content analysis and the “Organizational Culture Assessment Instrument” developed by Cameron and Quinn. On the basis of the results of a qualitative content analysis, the frequency of the categories of quality culture parameters in the literature was determined; with the help of the method of logical analysis and comparative analysis, the factors of quality culture corresponding to the parameters – dominant features, organizational leadership, employee management, organization glue, strategic goals and success criteria – were identified. An organizational culture based on quality culture principles is a significant factor for utilization of organizational competencies, creating an effective management and resource-oriented approach that is implemented focusing on the organization’s long-term interests and goals. By adopting a total quality management philosophy in the organization’s operations, the company can become more competitive, creating a working environment in which every employee can contribute, as well as facilitating cooperation between team members.